Harvard Business Review Emotional Intelligence Collection - Review, Harvard (Ascent Audio, 2020)
How to be human at work. Each book in the HBR's Emotional Intelligence series offers proven research showing how our emotions impact our work lives, practical advice for managing difficult people and situations, and inspiring essays on what it means to tend to our emotional well-being at work. Uplifting and practical, these books describe the social skills that are critical for ambitious professionals to master. This four-volume set includes Happiness, Resilience, Mindfulness, and Empathy.